Magnesium alloy hydrogen storage material and preparation method thereof
By adding cerium elements and other transition metals to the magnesium alloy, stable CeH2.73 compounds and alloys are generated, combined with a staged smelting procedure, the problem of poor thermodynamic and kinetic properties of magnesium hydride is solved, and magnesium-based hydrogen storage materials are improved The hydrogen charge and discharge performance and production efficiency achieve low-cost and efficient preparation of hydrogen storage materials.
Patent Information
- Application Number
- CN202411415489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The high thermodynamic stability and poor kinetic properties of magnesium hydride limit its widespread use in industrial applications. The commercial production and practical application of nanomagnesium-based hydrogen storage materials face high costs, low hydrogen storage capacity and poor cycle stability. The problem.
The chemical formula of the hydrogen storage material of magnesium alloy is Mg100-a-b-x-yNiaZrbNaxCey, and the stable CeH2.73 compound is generated as a catalyst by adding cerium elements, reducing the activation energy of the magnesium-based material, and forming an alloy with magnesium through nickel, zirconium and sodium, reducing the The temperature requirements for hydrogen absorption and hydrogen release are prepared in combination with the smelting procedure of phased heating and insulation.
It significantly improves the migration rate and efficiency of hydrogen atoms, reduces the activation energy of magnesium-based materials, improves the charge and discharge performance, improves the kinetic performance, and avoids uneven material properties or defects through precise temperature control, and improves production efficiency and the density of the material.
Smart Images

Figure CN119287234A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage alloys, and in particular to a magnesium alloy hydrogen storage material and a preparation method thereof. Background Art
[0002] Magnesium hydride (MgH2) has a high theoretical weight hydrogen storage density (7.6wt% H2) and volume hydrogen storage density (110kgH2 / m 3 ), as well as the abundant reserves and low cost of magnesium metal, it is regarded as an ideal hydrogen storage material. However, the high thermodynamic stability and poor kinetic performance of magnesium hydride limit its widespread use in practical industrial applications.
[0003] To overcome these challenges, researchers have adopted a variety of strategies to improve the hydrogen storage properties of magnesium hydride. Among them, alloying magnesium with transition metals is an effective strategy. By adding transition metals, the thermodynamic stability of magnesium hydride can be reduced, thereby reducing the temperature requirements for its hydrogen absorption and desorption. In addition, the addition of transition metals can also improve the kinetic properties of magnesium hydride and accelerate the rate of hydrogen absorption and desorption.
[0004] Transition metals such as nickel (Ni), cobalt (Co), and iron (Fe) can reduce the activation energy of magnesium hydride and improve its kinetic properties through a variety of mechanisms. For example, transition metals can form stronger chemical bonds with hydrogen, thereby reducing the energy of the Mg-H bond. In addition, transition metals can also promote the splitting of H2 molecules, making hydrogen easier to absorb and release.
[0005] In addition to alloying, nanotechnology is also used to improve the performance of magnesium-based hydrogen storage materials. By preparing magnesium hydride into nanoparticles, the specific surface area of the material can be increased, providing more active sites, thereby improving its hydrogen absorption and desorption kinetics. Nanostructured magnesium hydride can achieve reversible hydrogen absorption and desorption at lower temperatures, which makes it possible to achieve low-temperature, efficient solid-state hydrogen storage.
[0006] Despite significant progress, the commercial large-scale production and practical application of nano-magnesium-based hydrogen storage materials still face challenges. Future research needs to further reduce the cost of hydrogen storage materials, improve their hydrogen storage capacity and cycle stability, and develop more efficient synthesis methods.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] One of the objectives of the present invention is to provide a magnesium alloy hydrogen storage material to alleviate at least one of the above technical problems.
[0009] A second object of the present invention is to provide a method for preparing a magnesium alloy hydrogen storage material.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The first aspect of the present invention provides a magnesium alloy hydrogen storage material, the chemical formula of which is Mg 100-a-b-x-y Ni a Zr b Na x Ce y ;
[0012] Among them, 10≤a≤20; 0.1≤b≤2; 0.1≤x≤2; 1≤y≤15.
[0013] Furthermore, Mg 100-a-b-x-y Ni a Zr b Na x Ce y In the formula, 10≤a≤15; 0.5≤b≤1; 0.5≤x≤1; 3≤y≤10.
[0014] The second aspect of the present invention provides a method for preparing the magnesium alloy hydrogen storage material, wherein the magnesium alloy hydrogen storage material is prepared according to the ratio of each element in the magnesium alloy hydrogen storage material, and then the raw materials are smelted to obtain the magnesium alloy hydrogen storage material;
[0015] Wherein, the smelting is carried out according to the following procedure:
[0016] The temperature is raised from room temperature to the first temperature at a first heating rate and kept at that temperature for 5 to 15 minutes; then the temperature is raised to the second temperature at a second heating rate and kept at that temperature for 5 to 15 minutes; finally, the temperature is raised to the third temperature at a third heating rate and kept at that temperature for 1 to 10 minutes.
[0017] Furthermore, the raw material includes at least one of magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles.
[0018] Furthermore, the raw material also includes a drying process before smelting.
[0019] Preferably, the drying temperature is 140-160° C. and the drying time is 20-40 min.
[0020] Furthermore, the first heating rate is 1-10° C. / min.
[0021] Preferably, the first temperature is 680-720°C.
[0022] Furthermore, the second heating rate is 1-10° C. / min.
[0023] Preferably, the second temperature is 720-730°C.
[0024] Furthermore, the third heating rate is 1-10°C / min.
[0025] Preferably, the third temperature is 730-740°C.
[0026] Furthermore, the smelting is carried out in a smelting furnace.
[0027] Preferably, the smelting furnace is deoxygenated and denitrogenated before the smelting.
[0028] Preferably, argon gas replacement is used to remove oxygen and nitrogen.
[0029] Preferably, after deoxygenation and denitrification and before smelting, the pressure in the smelting furnace is -0.08 to -0.05 MPa.
[0030] Furthermore, the smelting is carried out according to the following procedure:
[0031] The temperature is raised from room temperature to 680-720°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; then the temperature is raised to 720-730°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; finally, the temperature is raised to 730-740°C at a rate of 1-10°C / min, and kept warm for 1-10 minutes.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] The magnesium alloy hydrogen storage material provided by the present invention has cerium added to the magnesium alloy. The cerium element reacts with hydrogen to generate stable CeH2.73. This compound always exists during the entire hydrogen charging and discharging process, providing an additional channel for the diffusion of hydrogen atoms, and significantly improving the rate and efficiency of hydrogen atom migration. This stable compound acts as a catalyst, reduces the activation energy of the magnesium-based material, promotes the adsorption and release of hydrogen, and thus improves the hydrogen charging and discharging performance. Other metal elements nickel, zirconium and sodium form alloys with magnesium, reducing the temperature requirements for hydrogen absorption and desorption. The presence of nickel, zirconium and sodium also helps to crack H2 molecules, increases the adsorption rate of hydrogen, and further improves the kinetic properties of the magnesium-based alloy.
[0034] The preparation method of the magnesium alloy hydrogen storage material provided by the present invention ensures accurate temperature control during the alloy smelting process by adopting a melting procedure of heating up and keeping warm in stages, thereby avoiding uneven material properties or defects caused by excessive temperature fluctuations. The preparation method is safe, reliable and easy to operate. In addition, the method is short in time, and the conversion efficiency from preparation to finished product is high, which greatly improves the production rate and lays a solid foundation for large-scale production and wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 The metallographic structure of the magnesium alloy hydrogen storage material provided in Example 1;
[0037] Figure 2 The metallographic structure of the magnesium alloy hydrogen storage material provided in Comparative Example 1;
[0038] Figure 3 The XRD patterns of hydrogen absorption and desorption of the magnesium alloy hydrogen storage material obtained in Example 1;
[0039] Figure 4 This is the hydrogen release curve obtained in Test Example 3. DETAILED DESCRIPTION
[0040] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] The first aspect of the present invention provides a magnesium alloy hydrogen storage material, the chemical formula of which is Mg 100-a-b-x-y Ni a Zr b Na x Ce y ;
[0042] Among them, 10≤a≤20; 0.1≤b≤2; 0.1≤x≤2; 1≤y≤15.
[0043] Furthermore, Mg 100-a-b-x-y Ni a Zr b Na x Ce y In the formula, 10≤a≤15; 0.5≤b≤1; 0.5≤x≤1; 3≤y≤10.
[0044] The magnesium alloy hydrogen storage material provided by the present invention has cerium added to the magnesium alloy. The cerium element reacts with hydrogen to generate stable CeH2.73. This compound always exists during the entire hydrogen charging and discharging process, providing an additional channel for the diffusion of hydrogen atoms, and significantly improving the rate and efficiency of hydrogen atom migration. This stable compound acts as a catalyst, reduces the activation energy of the magnesium-based material, promotes the adsorption and release of hydrogen, and thus improves the hydrogen charging and discharging performance. Other metal elements nickel, zirconium and sodium form alloys with magnesium, reducing the temperature requirements for hydrogen absorption and desorption. The presence of nickel, zirconium and sodium also helps to crack H2 molecules, increases the adsorption rate of hydrogen, and further improves the kinetic properties of the magnesium-based alloy.
[0045] Typically, but not limiting, the chemical formula of the magnesium alloy hydrogen storage material may be, for example, Mg 85 Ni 10 ZrNaCe3、Mg 83 Ni 12 ZrNaCe3、Mg 83 Ni 10 ZrNaCe5、Mg 82 Ni 12 Zr 0.5 Na 0.5 Ce5、Mg 81 Ni 10 ZrNaCe5 or Mg 80 Ni 12 Zr 0.5 Na 0.5 Ce7.
[0046] The second aspect of the present invention provides a method for preparing the magnesium alloy hydrogen storage material, wherein the magnesium alloy hydrogen storage material is prepared according to the ratio of each element in the magnesium alloy hydrogen storage material, and then the raw materials are smelted to obtain the magnesium alloy hydrogen storage material;
[0047] Wherein, the smelting is carried out according to the following procedure:
[0048] The temperature is raised from room temperature to the first temperature at a first heating rate and kept at that temperature for 5 to 15 minutes; then the temperature is raised to the second temperature at a second heating rate and kept at that temperature for 5 to 15 minutes; finally, the temperature is raised to the third temperature at a third heating rate and kept at that temperature for 1 to 10 minutes.
[0049] The preparation method of the magnesium alloy hydrogen storage material provided by the present invention ensures accurate temperature control during the alloy smelting process by adopting a melting procedure of heating up and keeping warm in stages, thereby avoiding uneven material properties or defects caused by excessive temperature fluctuations. The preparation method is safe, reliable and easy to operate. In addition, the method is short in time, and the conversion efficiency from preparation to finished product is high, which greatly improves the production rate and lays a solid foundation for large-scale production and wide application.
[0050] Furthermore, the raw material includes at least one of magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles.
[0051] Furthermore, the raw material also includes a drying process before smelting. By removing the moisture in the raw material, the oxidation caused by the rapid evaporation of moisture during the heating process can be prevented. This oxidation will not only reduce the purity of the magnesium alloy hydrogen storage material, but may also produce slag, affecting the quality of the smelting product. At the same time, drying the raw material helps to reduce the porosity problem during the smelting process, because the gas generated by the evaporation of water will form bubbles in the alloy. If these bubbles are trapped inside the magnesium alloy hydrogen storage material, they will reduce the density and mechanical properties of the material. In addition, drying the raw material can also improve the safety and efficiency of smelting, and avoid the splashing of the melt caused by the evaporation of water. Such splashing will not only affect the stability of the smelting process, but may also pose a safety risk to the operator. By ensuring the drying of the raw materials, the chemical reactions in the smelting process can be more accurately controlled, thereby improving the performance and yield of the alloy.
[0052] Preferably, the drying temperature is 140-160° C. and the drying time is 20-40 min.
[0053] Typically but not limiting, the temperature of the drying process may be, for example, 140° C., 145° C., 150° C., 155° C. or 160° C. Similarly, the drying time is between 20 minutes and 40 minutes, and the specific time may also be any value within this range, such as 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes.
[0054] Furthermore, the first heating rate is 1-10° C. / min.
[0055] Typically but not limiting, the first heating rate is set between 1°C / min and 10°C / min, but can also be any value within this range, such as 1°C / min, 5°C / min, 8°C / min or 10°C / min.
[0056] Preferably, the first temperature is 680-720°C.
[0057] Typically but not limiting, the first temperature ranges from 680°C to 720°C, which means that the first temperature can be any temperature value within this interval, such as 680°C, 690°C, 700°C, 710°C, 720°C.
[0058] The temperature is raised from room temperature to a first temperature of 680-720°C at a first heating rate of 1-10°C / min and maintained for 5-15 minutes. During this process, cerium and nickel in the raw materials are dissolved into the crystal lattice of magnesium as solute atoms to form a uniformly mixed solid solution that still maintains the magnesium crystal structure type.
[0059] Furthermore, the second heating rate is 1-10° C. / min.
[0060] Typically but not limitatively, the second heating rate is also in the range of 1°C / min to 10°C / min, and specific values may be 1°C / min, 2°C / min, 5°C / min, 8°C / min or 10°C / min.
[0061] Preferably, the second temperature is 720-730°C.
[0062] Typically but not limiting, the second temperature ranges from 720°C to 730°C, which means the second temperature may be any temperature value within this interval, such as 720°C, 725°C or 730°C.
[0063] The temperature is raised to a second temperature of 720-730° C. at a second heating rate of 1-10° C. / min and maintained for 5-15 minutes. In this process, sodium in the raw material will occupy the space lattice of Ce atoms due to its smallest atomic mass, forming an interstitial solid solution during the melting process.
[0064] Furthermore, the third heating rate is 1-10°C / min.
[0065] Typically but not limitatively, the third heating rate is also between 1°C / min and 10°C / min, and specifically may be 1°C / min, 2°C / min, 5°C / min, 8°C / min or 10°C / min.
[0066] Preferably, the third temperature is 730-740°C.
[0067] Typically but not limiting, the third temperature ranges from 730°C to 740°C, which means that the third temperature can be any temperature value within this interval, such as 730°C, 735°C or 740°C.
[0068] The temperature is raised to a third temperature of 730-740° C. at a third heating rate of 1-10° C. / min and maintained for 1-10 minutes. During this process, the magnesium-zirconium alloy in the raw material reaches its melting temperature and is mixed and melted with the magnesium solid solution LPSO.
[0069] Furthermore, the smelting is carried out in a smelting furnace.
[0070] Preferably, the smelting furnace is deoxygenated and denitrified before the smelting to ensure the quality and purity of the magnesium alloy hydrogen storage material during the smelting process. By removing oxygen and nitrogen from the atmosphere in the furnace, the possibility of the metal reacting with these gases during the smelting process can be significantly reduced, thereby preventing the generation of unnecessary oxides and nitrides. These compounds may affect the microstructure of the magnesium alloy hydrogen storage material, resulting in a decrease in material properties, such as strength, toughness and corrosion resistance.
[0071] In addition, removing oxygen helps reduce oxidation losses of metals during the smelting process, improves raw material utilization and smelting efficiency. At the same time, an oxygen-free and nitrogen-free smelting environment can reduce the risk of metal inhalation during the smelting process, which will form pores that may cause defects during subsequent processing and use.
[0072] Preferably, argon gas replacement is used to remove oxygen and nitrogen.
[0073] Preferably, after deoxygenation and denitrification and before smelting, the pressure in the smelting furnace is -0.08 to -0.05 MPa.
[0074] Typically but not limiting, the pressure in the smelting furnace may be, for example, -0.08 MPa, -0.07 MPa, -0.06 MPa or -0.05 MPa, or any value within the range of -0.08 to -0.05 MPa.
[0075] Furthermore, the smelting is carried out according to the following procedure:
[0076] The temperature is raised from room temperature to 680-720°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; then the temperature is raised to 720-730°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; finally, the temperature is raised to 730-740°C at a rate of 1-10°C / min, and kept warm for 1-10 minutes.
[0077] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0078] Example 1
[0079] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0080] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0081] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0082] In the first stage, the temperature was raised from room temperature to 700 °C at a heating rate of 5 °C / min and kept at that temperature for 10 min.
[0083] In the second stage, the temperature was raised from 700°C to 720°C at a heating rate of 2°C / min and kept at this temperature for 10 min.
[0084] In the third stage, the temperature was raised from 720°C to 730°C at a heating rate of 2°C / min and kept at this temperature for 5 min.
[0085] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0086] Example 2
[0087] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 85 Ni 10 ZrNaCe3. The preparation method is the same as that in Example 1 and will not be described in detail here.
[0088] Example 3
[0089] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 80 Ni 12 Zr 0.5 Na 0.5 Ce7. The preparation method is the same as that in Example 1 and will not be described in detail here.
[0090] Example 4
[0091] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 82 Ni 12 Zr 0.5 Na 0.5 The preparation method of Ce5 is the same as that of Example 1 and will not be described in detail here.
[0092] Example 5
[0093] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 81 Ni 12 ZrNaCe5. The preparation method is the same as that in Example 1 and will not be described in detail here.
[0094] Example 6
[0095] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0096] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0097] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0098] In the first stage, the temperature was raised from room temperature to 680°C at a heating rate of 5°C / min and kept at that temperature for 5 min.
[0099] In the second stage, the temperature was increased from 680°C to 720°C at a heating rate of 5°C / min and kept at this temperature for 10 min.
[0100] In the third stage, the temperature was raised from 720°C to 730°C at a heating rate of 5°C / min and kept at this temperature for 10 min.
[0101] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0102] Example 7
[0103] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0104] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0105] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0106] In the first stage, the temperature was raised from room temperature to 690°C at a heating rate of 10°C / min and kept at that temperature for 8 min.
[0107] In the second stage, the temperature was raised from 690°C to 720°C at a heating rate of 3°C / min and kept at this temperature for 8 min.
[0108] In the third stage, the temperature was raised from 720°C to 730°C at a heating rate of 3°C / min and kept at this temperature for 10 min.
[0109] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0110] Example 8
[0111] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0112] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0113] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0114] In the first stage, the temperature was raised from room temperature to 710°C at a heating rate of 10°C / min and kept at that temperature for 10 min.
[0115] In the second stage, the temperature was increased from 710°C to 725°C at a heating rate of 5°C / min and kept at this temperature for 5 min.
[0116] In the third stage, the temperature was raised from 725°C to 735°C at a heating rate of 5°C / min and kept at that temperature for 8 min.
[0117] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0118] Example 9
[0119] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0120] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0121] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0122] In the first stage, the temperature was raised from room temperature to 720°C at a heating rate of 10°C / min and kept at that temperature for 10 min.
[0123] In the second stage, the temperature was increased from 720°C to 740°C at a heating rate of 5°C / min and kept at this temperature for 10 min.
[0124] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0125] Example 10
[0126] This embodiment provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 83 Ni 10 ZrNaCe5. The preparation method is as follows:
[0127] 1. According to the ratio of elements in the chemical formula, weigh magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles, put them into a forced air drying oven at 150°C and dry them for 30 minutes.
[0128] 2. Put the dried raw materials into the melting crucible, lock and seal the melting furnace, and maintain a slight negative pressure of -0.05MPa after three argon replacements in the furnace. Start setting the heating program:
[0129] The temperature was raised from room temperature to 740°C at a heating rate of 10°C / min and kept at this temperature for 10 min.
[0130] After smelting, the alloy liquid is poured into a water-cooled crucible and an alloy ingot is obtained after cooling.
[0131] Comparative Example 1
[0132] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 88 Ni 10 The preparation method is the same as that in Example 1 and will not be described in detail here.
[0133] Comparative Example 2
[0134] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 84 Ni 10 The preparation method of ZrCe5 is the same as that in Example 1 and will not be repeated here.
[0135] Comparative Example 3
[0136] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 84 Ni 10 The preparation method of NaCe5 is the same as that in Example 1 and will not be repeated here.
[0137] Comparative Example 4
[0138] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg93 The preparation method of ZrNaCe5 is the same as that in Example 1 and will not be repeated here.
[0139] Comparative Example 5
[0140] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 89 Ni 10 The preparation method is the same as that in Example 1 and will not be described in detail here.
[0141] Comparative Example 6
[0142] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 89 Ni 10 The preparation method is the same as that in Example 1 and will not be described in detail here.
[0143] Comparative Example 7
[0144] This comparative example provides a magnesium alloy hydrogen storage material, whose chemical formula is Mg 85 Ni 10 The preparation method of Ce5 is the same as that of Example 1 and will not be described in detail here.
[0145] Characterization Example 1
[0146] The magnesium alloy hydrogen storage materials obtained in Example 1 and Comparative Example 1 were used to make metallographic structures, and a method magnification of 500 times was selected. The obtained pictures corresponded to the following: Figure 1 and Figure 2 shown.
[0147] from Figure 1 and Figure 2 It can be seen that the grain size of the sample containing cerium is smaller and the uniformity is better. Since the refinement of the sample grain size shortens the diffusion distance of hydrogen and increases the contact area, it is beneficial to the hydrogen absorption and desorption performance of the sample.
[0148] Characterization Example 2
[0149] The magnesium alloy hydrogen storage material obtained in Example 1 was charged with hydrogen, and XRD was performed after reaching a saturated state; then hydrogen was released, and XRD was continued after the hydrogen was completely released. The obtained spectrum corresponds to the following: Figure 3 shown.
[0150] from Figure 3 It can be seen that the excellent hydrogen charging and dehydrogenation performance of Example 1 is mainly due to the generation of stable CeH2.73 during the first hydrogen charging, which exists in the entire subsequent hydrogen charging and dehydrogenation process, provides more channels for the diffusion of hydrogen atoms, and has a catalytic effect on improving the hydrogen charging and dehydrogenation performance of magnesium-based materials.
[0151] Test Example 1
[0152] DSC Testing
[0153] Test samples: magnesium alloy hydrogen storage materials of the embodiments and comparative examples.
[0154] Test method: A thermogravimetric analyzer is used to test the sample that has reached saturation with hydrogen absorption at different heating rates to obtain the peak hydrogen desorption temperature at different heating rates.
[0155] The test results are shown in Table 1 below:
[0156] Table 1
[0157]
[0158]
[0159] As shown in Table 1, the DSC test results of the magnesium alloy of the embodiment show that at different heating rates, the peak temperature at a heating rate of 5°C / min drops to below 351.2°C, the peak temperature at a heating rate of 10°C / min drops to below 360.8°C, the peak temperature at a heating rate of 15°C / min drops to below 395.6°C, and the peak temperature at a heating rate of 20°C / min drops to below 411.6°C. This indicates that the peak temperature of hydrogen desorption of the magnesium alloy material provided by the present invention is significantly reduced, and the thermodynamic properties are significantly improved.
[0160] Test Example 2
[0161] Hydrogen absorption and desorption kinetic cycle stability test
[0162] Test sample: magnesium alloy hydrogen storage material provided in the examples and comparative examples.
[0163] Test method: The sample was subjected to a hydrogen absorption and desorption cycle stability test at a fixed temperature of 350°C and a fixed hydrogen pressure of 3.0 MPa. The hydrogen absorption and desorption time were both 15 minutes.
[0164] The test results are shown in Table 2 below:
[0165] Table 2
[0166]
[0167]
[0168] As shown in Table 2, the magnesium alloy material of the embodiment and the preparation method thereof have stable hydrogen storage cycle dynamic performance. Within the initial 15 minutes, the alloy absorbed 6.303wt.%H2, and after 10 cycles, the hydrogen absorption capacity was 6.116wt.%H2, and the retention rate of the hydrogen absorption capacity was above 97.0%. Within the initial 15 minutes, the alloy released 6.148wt.%H2, and after 10 cycles, the hydrogen release capacity was 5.962wt.%H2, and the retention rate of the hydrogen release capacity was still above 97.0%.
[0169] Test Example 3
[0170] The hydrogen-saturated magnesium alloy hydrogen storage materials of Example 1 and Comparative Example 1 were subjected to a hydrogen desorption experiment.
[0171] The specific steps are as follows: the hydrogen-saturated sample of Example 1 releases hydrogen at 250° C. and 0 MPa for 120 min; the hydrogen-saturated sample of Comparative Example 1 releases hydrogen at 270° C. and 0 MPa for 120 min.
[0172] The hydrogen release curve corresponds to Figure 4 shown.
[0173] from Figure 4 It can be seen that within the same 120 min, the hydrogen desorption rate and amount of the sample with cerium added at 250°C are much greater than the hydrogen desorption rate and amount of the alloy sample without cerium added at 270°C.
[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A magnesium alloy hydrogen storage material, characterized in that: The chemical formula of the magnesium alloy hydrogen storage material is Mg 100-a-b-x- y Ni a Zr b Na x Ce y ; Among them, 10≤a≤20; 0.1≤b≤2; 0.1≤x≤2; 1≤y≤15.
2. The magnesium alloy hydrogen storage material according to claim 1, characterized in that: 10≤a≤15; 0.5≤b≤1; 0.5≤x≤1; 3≤y≤10.
3. A method for preparing the magnesium alloy hydrogen storage material according to claim 1 or 2, characterized in that: The magnesium alloy hydrogen storage material is prepared according to the ratio of each element in the magnesium alloy hydrogen storage material, and then the raw materials are smelted to obtain the magnesium alloy hydrogen storage material; Wherein, the smelting is carried out according to the following procedure: The temperature is raised from room temperature to the first temperature at a first heating rate and kept at that temperature for 5 to 15 minutes; then the temperature is raised to the second temperature at a second heating rate and kept at that temperature for 5 to 15 minutes; finally, the temperature is raised to the third temperature at a third heating rate and kept at that temperature for 1 to 10 minutes.
4. The preparation method according to claim 3, characterized in that: The raw material includes at least one of magnesium-nickel alloy, magnesium-zirconium alloy, magnesium-sodium alloy, cerium particles and magnesium particles.
5. The preparation method according to claim 3, characterized in that: The raw materials also include a drying process before smelting; Preferably, the drying temperature is 140-160° C. and the drying time is 20-40 min.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The first heating rate is 1 to 10°C / min; Preferably, the first temperature is 680-720°C.
7. The preparation method according to any one of claims 3 to 5, characterized in that: The second heating rate is 1 to 10°C / min; Preferably, the second temperature is 720-730°C.
8. The preparation method according to any one of claims 3 to 5, characterized in that: The third heating rate is 1-10°C / min; Preferably, the third temperature is 730-740°C.
9. The preparation method according to any one of claims 3 to 5, characterized in that: Carrying out the smelting in a smelting furnace; Preferably, the smelting furnace is deoxygenated and denitrified before the smelting; Preferably, argon gas replacement is used to remove oxygen and nitrogen; Preferably, after deoxygenation and denitrification and before smelting, the pressure in the smelting furnace is -0.08 to 0.05 MPa.
10. The preparation method according to claim 3, characterized in that: The smelting is carried out according to the following procedure: The temperature is raised from room temperature to 680-720°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; then the temperature is raised to 720-730°C at a rate of 1-10°C / min, and kept warm for 5-15 minutes; finally, the temperature is raised to 730-740°C at a rate of 1-10°C / min, and kept warm for 1-10 minutes.
Citation Information
Patent Citations
Magnesium alloys for hydrogen storage
CN101120111A
Activation-free high-capacity magnesium-based hydrogen storage alloy and preparation method thereof
CN116516192A
Mg-base hydrogen-bearing alloy material and its preparing process and application
CN1316537A
Cited By
Magnesium-based hydrogen storage material and preparation method thereof
CN117985653A